Routine revascularization with percutaneous coronary intervention in patients with coronary artery disease undergoing transcatheter aortic valve implantation – the third nordic aortic valve intervention trial – NOTION-3 - Sabbah Muhammad; Veien Karsten; Niemelä Matti; Freeman Philip; Linder Rickard; Ioanes Dan; Terkelsen Christian Juhl; Kajander Olli A.; Koul Sasha; Savontaus Mikko; Karjalainen Pasi; Erglis Andrejs; et al. (Elsevier Inc., 2025)
Background: Coronary artery disease (CAD) frequently coexists with severe aortic valve stenosis (AS) in patients planned for transcatheter aortic valve implantation (TAVI). How to manage CAD in this patient population is still an unresolved question. In particular, it is still not known whether fractional flow reserve (FFR) guided revascularization with percutaneous coronary intervention (PCI) is superior to medical treatment for CAD in terms of clinical outcomes.
Study design: The third Nordic Aortic Valve Intervention (NOTION-3) Trial is an open-label investigator-initiated, multicenter multinational trial planned to randomize 452 patients with severe AS and significant CAD to either FFR-guided PCI or medical treatment, in addition to TAVI. Patients are eligible for the study in the presence of at least 1 significant PCI-eligible coronary stenosis. A significant stenosis is defined as either FFR ≤0.80 and/or diameter stenosis >90%. The primary end point is a composite of first occurring all-cause mortality, myocardial infarction, or urgent revascularization (PCI or coronary artery bypass graft performed during unplanned hospital admission) until the last included patient have been followed for 1 year after the TAVI.
Summary: NOTION-3 is a multicenter, multinational randomized trial aiming at comparing FFR-guided revascularization vs medical treatment of CAD in patients with severe AS planned for TAVI.